Association between multidrug resistance-1 C3435T gene polymorphism and right ventricular dysfunction in patients with chronic obstructive pulmonary disease: cross-sectional study - Oğuzhan Yücel; Hakan Güneş; Hasan Yücel; Ali Zorlu (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Right ventricular (RV) dysfunction may develop over the course of chronic obstructive pulmonary disease (COPD) and is an important predictor of morbidity and mortality. Polymorphism of the multidrug resistance-1 (MDR-1) gene has been correlated with worse clinical findings among patients with COPD. Our aim here was to investigate the relationship between MDR-1 C3435T gene polymorphism and RV dysfunction in COPD patients. DESIGN AND SETTING: This was a cross-sectional study investigating the relationship between RV dysfunction and genetic defects in COPD patients. METHODS: Forty-one consecutive patients diagnosed with COPD and hospitalized due to acute exacerbation were enrolled. Polymorphism was analyzed using the strip assay technique. RV parameters were evaluated, and RV dysfunction was identified via transthoracic echocardiography. Patients were categorized into three groups according to gene polymorphism: MDR-1 CC (wild type, n = 9), MDR-1 CT (heterozygote mutant, n = 21) or MDR-1 TT (homozygote mutant, n = 11). RESULTS: The study included 14 males and 27 females (mean age 65 ± 11 years). The mean systolic pulmonary artery pressure was 31.4 ± 8 mmHg in the wild-type group, 42.2 ± 12 mmHg in the heterozygote mutant group and 46.5±14 mmHg in the homozygote mutant group (P = 0.027). Presence of RV dilatation was significantly different among the three groups (33%, 71%, and 100%, respectively; P = 0.005). In multiple logistic regression analysis, MDR-1 C3435T gene polymorphism (OR = 9.000, P = 0.019) was an independent predictor of RV dysfunction after adjustment for potential confounders. CONCLUSION: MDR-1 C3435T gene polymorphism was associated with RV dysfunction in patients with COPD.